The Quantitative Nature of the Body Ettawa crossbreed goats in Lactation 2 and 3 in the P4S Agribusiness Group Assalam Indihiang Tasikmalaya Regency - Raden Febrianto Christi; Dwi Suharwanto (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The ettawa crossbreed goat is a crossbreed goat between etawa goats from India and native Indonesian goats. The quantitative nature of the body in livestock is very important to know because it can predict the ability in productivity. This research was conducted at the Goat Farming Group P4S Agribusiness Assalam Indihiang Tasikmalaya Regency. The study aims to determine the quantitative nature that includes body length, chest circumference, and height in etawa crossbreed goats in the lactation period 2 and 3. The research method used is quantitative descriptive analysis with the object of etawa crossbreed goat research in the lactation period 2 and 3. The results show that in the lactation period 2 obtained an average body length of 78 cm coefficient of variation 0.090%, chest circumference 93.25 cm coefficient of variation 0.049%, and height 57.5 cm coefficient of variation 0.012%, on lactation 3 an average body length of 75, 83 cm coefficient of variation 0.05%, chest circumference 93 cm coefficient of variation 0.028%, height 57.53 cm coefficient of variation 0.012%. The conclusion states that the body size characteristics of dairy goats in the lactation periods 2 and 3 are in accordance with the existing Indonesian National Standards (SNI).